Shift of Criminal Liability in Unauthorized Oil Mining Offenses Towards Realizing The Welfare of The People - Elly Sudarti; Nys Arfa; Pahlefi; Sahuri Lasmadi (Faculty of Law, Universitas Pekalongan, 2025)
This research has the purpose to: This research is motivated by the absence of a supervision system for oil mining permits and the occurrence of norm shifts in criminal sentencing for unauthorized oil mining offenses, resulting in a lack of clarity in procedures and processes regarding the imposition of criminal sanctions. The issues in this research are as follows: (1) How is the Concept of Criminal Liability in Unauthorized Oil Mining Offenses Framed to Achieve the Welfare of the People? (2) Can the Shift in Norms Regarding the Concept of Criminal Liability in Unauthorized Oil Mining Offenses Contribute to the Welfare of the People? Research Methodology: (1) Normative juridical research type. Analysis of Legal Materials: The obtained legal materials are inventoried and subsequently analyzed qualitatively, providing descriptions of results that prioritize the quality of legal materials. The method of legal material analysis employed is systematic interpretation. Drawing conclusions from the analysis results is conducted using the deductive method, which involves inferring research outcomes from general principles to specific instances. The intended results include discovering a formulation regarding a supervision system for oil mining permits and elaborating on the concept of shifting criminal liability in imposing penalties for unauthorized oil mining offenses, resulting in the lack of clarity regarding procedures and processes for imposing criminal sanctions. This research has the purpose to: This research is motivated by the absence of a supervision system for oil mining permits and the occurrence of norm shifts in criminal sentencing for unauthorized oil mining offenses, resulting in a lack of clarity in procedures and processes regarding the imposition of criminal sanctions. The issues in this research are as follows: (1) How is the Concept of Criminal Liability in Unauthorized Oil Mining Offenses Framed to Achieve the Welfare of the People? (2) Can the Shift in Norms Regarding the Concept of Criminal Liability in Unauthorized Oil Mining Offenses Contribute to the Welfare of the People? Research Methodology: (1) Normative juridical research type. Analysis of Legal Materials: The obtained legal materials are inventoried and subsequently analyzed qualitatively, providing descriptions of results that prioritize the quality of legal materials. The method of legal material analysis employed is systematic interpretation. Drawing conclusions from the analysis results is conducted using the deductive method, which involves inferring research outcomes from general principles to specific instances. The intended results include discovering a formulation regarding a supervision system for oil mining permits and elaborating on the concept of shifting criminal liability in imposing penalties for unauthorized oil mining offenses, resulting in the lack of clarity regarding procedures and processes for imposing criminal sanctions.